Full-length KIR3DL1*022 detected in an African donor - Yindom, L; James, K; de Silva, T; Rowland-Jones, S (Blackwell Publishing Ltd, 2014)
KIR3DL1*022 is significantly different from the most common West African allele - KIR3DL1*01501.